Constructing an Evaluation Framework and Developing Optimization Strategies for Public Cultural Service Spaces in Metro Station Areas: A Scene Theory - Chulin Lu; Yajun Cai; Muchuan Xu (Urban Science, 2026)
Metro station areas are transitioning from single-purpose transportation transfer nodes into multifunctional public spaces that integrate public services, cultural displays, and place-based experiences. However, there remains a lack of systematic evaluation tools for assessing public cultural service quality in metro station areas that integrate cultural meanings, public identity, and experiential expressions. An Analytic Network Process (ANP) network structure was established based on expert judgments to determine the weights, and Technigue for Order Preference by Similarity to Ideal Solution (TOPSIS) was applied for comprehensive evaluation and ranking using the scores provided by professional evaluators for 13 sampled stations in Foshan, Xi’an, and Shenzhen. Analytic Hierarchy Process (AHP)-TOPSIS was used for robustness testing, and dimensional weight perturbation analysis was conducted to assess model stability. Six types of Point of interests (POIs) were further incorporated to characterize the external functional contexts of the sampled stations. The results showed that the weights of Authenticity, Legitimacy, and Theatricality were 0.498, 0.296, and 0.206, respectively. Traditional, Self-expressive, Charismatic, Exhibitionistic, and Utilitarian were identified as the key indicators with relatively high weights. The 13 sampled stations showed significant differences in overall performance. Higher-performing cases demonstrated more balanced performance across the three scene dimensions of Authenticity, Legitimacy, and Theatricality. In contrast, lower-performing cases showed relatively weaker performance on some key indicators. The robustness test based on AHP-substituted weights and Spearman correlation analysis verified the stability of the evaluation framework, while the sensitivity analysis showed that the evaluation results remained relatively stable under weight perturbations. This study extends the application of scene theory in metro station area research and provides an evaluation framework and practical reference for optimizing public cultural service spaces in transit-oriented urban environments.